Re-thinking inspiration as in-betweens in arts-integrated literacy practices - Jusslin, Sofia (Elsevier, 2022)
Inspiration is a widely used concept in everyday speech, and it is used especially when people talk about what they do in their creative processes. This article presents a re-thinking of the notion of inspiration through a non-representational approach to challenge the assumption of dance as a mere stimulus to and representation of texts and vice versa when integrating creative dance into literacy education. Based on diffractive analytical engagements, this article proposes an understanding of inspiration as intra-active and rhizomatic in-betweens producing new-ness and other-ness. This understanding can produce rich and diverse opportunities that value and cherish writing and dancing non-hierarchically in the literacy classroom; both have pedagogical value, without either acting as a servant of the other. The article concludes with a discussion of the extent to which literacy education is prepared to take dance seriously, emphasizing that the proposed understanding of inspiration can contribute to that end.
Keywords: tanssi; lukutaito; opetus; taidekasvatus